Designing and Fabricating a Handy Instrument for Measuring Clothing Pressure on the Human Body using MPX10DP Pressure Sensor - Phan, Thanh Thao; Vu, Xuan Hien (Old Journal, 2019)
This research introduces the design and fabrication of handy instrument which can measure the pressure of costume on the human body using a MPX10DP pressure sensor. The instrument operation is based on the sensing capacity of gaseous pressure transferred from a small airbag to the pressure sensor. Therefore, the device can measure pressure in many cases e.g. pressure applied to curvy surfaces like human parts. The device can communicate with a homemade software on the computer to display and record measured data via USB or Bluetooth communication method. The prototype device is calibrated by a pressure gauge named ALP K2 which is frequently used on commercial blood-pressure monitors. Finally, the accuracy and the data shift of the device during the operation is investigated and discussed.